1995
DOI: 10.1093/rheumatology/34.2.121
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Hypermobility Syndrome on Knee Joint Proprioception

Abstract: Proprioceptive sensory feedback is utilized by the central nervous system for conscious appreciation of the position and movement of the body and limbs. In patients with the hypermobility syndrome (HMS), it has been suggested that there is alteration of proprioceptive acuity. Proprioceptive performance of the knee joint was investigated in 10 female subjects who suffered from HMS using a threshold detection paradigm (accurate determination of the onset and direction of knee joint displacement at constant angul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
104
2
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(115 citation statements)
references
References 0 publications
2
104
2
3
Order By: Relevance
“…Proprioceptive acuity is abnormal in hypermobile joints, at both the PIP joint (18) and the knee joint (19). Position sense at the PIP joint was found to be significantly impaired in the setting of hypermobility; this is the same joint group in which we found a protective effect of hypermobility for OA.…”
Section: Discussionsupporting
confidence: 48%
“…Proprioceptive acuity is abnormal in hypermobile joints, at both the PIP joint (18) and the knee joint (19). Position sense at the PIP joint was found to be significantly impaired in the setting of hypermobility; this is the same joint group in which we found a protective effect of hypermobility for OA.…”
Section: Discussionsupporting
confidence: 48%
“…In patients diagnosed with joint hypermobility, studies have shown a higher correlation with ACL tear [28] and shoulder instability [4]. Joint hypermobility has also been associated with a disturbance in proprioception [20]. The combination of decreased proprioception in addition to abnormal biomechanical stresses believed to result from increased joint mobility [38] is theorized to contribute to the development of arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to joint laxity, patients with JHS have reduced joint receptor activation and therefore a disturbance in proprioception [27]. Hall et al [19] demonstrated proprioceptive performance in the subjects with JHS was considerably poorer in the midrange of motion compared with their age-and gender-matched control subjects. They hypothesized that this may be secondary to decreased feedback from joints and suggested neuromuscular training for these patients as a potential way to decrease future degenerative joint disease.…”
Section: Discussionmentioning
confidence: 99%
“…They hypothesized that this may be secondary to decreased feedback from joints and suggested neuromuscular training for these patients as a potential way to decrease future degenerative joint disease. These findings suggest a need to identify those with JHS who are at high risk for musculoskeletal injuries and institute programs in neuromuscular training to decrease their risk of long-term disability and osteoarthritis, both in the military and civilian populations [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation